2000
DOI: 10.7863/jum.2000.19.8.587
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of central venous pressure with Doppler waveform of the common femoral veins.

Abstract: The objects of this prospective study were to determine the nature of the flow in the right femoral vein and to correlate the flow velocity with the venous pressure measured in the right atrium. We performed 236 pulsed Doppler ultrasonographic examinations in 1 year on patients with a venous catheter with the distal tip in the right atrium. In the Doppler wave readouts we analyzed wave frequency, velocity components, and relationships among them and the existence of pulsatile flow. These parameters were then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…A similar study by Cozcolluela et al 11 looked at 236 patients and demonstrated a “significant inverse relation…. between pulsatile flow and high atrium pressure.” However, low sensitivity again precluded any recommendation as a screening tool for elevated central venous pressure.…”
Section: Discussionmentioning
confidence: 79%
“…A similar study by Cozcolluela et al 11 looked at 236 patients and demonstrated a “significant inverse relation…. between pulsatile flow and high atrium pressure.” However, low sensitivity again precluded any recommendation as a screening tool for elevated central venous pressure.…”
Section: Discussionmentioning
confidence: 79%
“…A follow-up study to this one found that when considered with evidence of “cardiac decompensation” on two consecutive chest radiographs, sensitivity increased to 79%. 16 In a similar study, Cozcolluela et al 17 looked at 236 patients and demonstrated a “significant inverse relation…. between pulsatile flow and high atrium pressure.” However, low sensitivity again precluded any recommendation as a screening tool for increased central venous pressure.…”
Section: Discussionmentioning
confidence: 93%
“…The largest study in which right heart catheterization and 236 CFV Doppler interrogations were performed showed a prevalence of 31% of pulsatile CFV Doppler signals. A significant correlation between the right atrial pressure and the CFV pulsatility index (PI) ([maximal–minimal velocity]/mean velocity) was reported ( 28 ). Alimoğlu et al ( 29 ) observed that the mean PI in patients with elevated right atrial pressure (7.75 ± 3.19) was significantly higher than in patients with normal right atrial pressure (1.55 ± 1.30; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The CFV is located inferior to the ileo-inguinal ligament and medial to the common femoral artery. Care should be taken to correctly identify the CFV and not one of its tributaries, such as the saphenous vein ( 27 , 28 ).…”
Section: How To Perform a Doppler Examination Of The Common Femoral Vmentioning
confidence: 99%